Development and Validation of HPLC and HPTLC Methods for Estimation of Glabridin in Extracts of Glycyrrhiza glabra. (27th November 2019) - Viswanathan, Vivek; Mukne, Alka P
Abstract: Glabridin is a major bioactive phytoconstituent of licorice. This work discusses the development and validation of HPLC and HPTLC methods for analysis of glabridin in licorice. The HPLC separation was performed using a Purospher STAR RP-18e column (5 μm silica particle size, 250 mm × 4.6 mm inner diameter) with gradient elution of 0.2% acetic acid in water–acetonitrile. The flow rate was 1 mL/min. Quantification was performed at a detection wavelength of 280 nm. HTPLC separation was performed on precoated silica gel 60 F254 aluminum plate (10 × 10 cm, 250 μm thickness). A linear ascending development was done using a mobile phase of hexane–ethyl acetate–chloroform (5 + 4 + 3, v/v/v). After development, the plates were scanned at 285 nm. Both of the methods provided good separation of glabridin from other constituents of licorice extract. The methods were validated as per ICH guidelines. Comparison by Student t -test showed that there was a statistically insignificant difference between the mean glabridin content estimated by both methods at 95% confidence interval. The glabridin content in licorice extract was 3.90% by HPLC and 3.79% by HPTLC.